2011
DOI: 10.1128/jvi.00667-11
|View full text |Cite
|
Sign up to set email alerts
|

Active Depletion of Host Cell Inhibitor-of-Apoptosis Proteins Triggers Apoptosis upon Baculovirus DNA Replication

Abstract: Apoptosis is an important antivirus defense by virtue of its impact on virus multiplication and pathogenesis. To define molecular mechanisms by which viruses are detected and the apoptotic response is initiated, we examined the antiviral role of host inhibitor-of-apoptosis (IAP) proteins in insect cells. We report here that the principal IAPs, DIAP1 and SfIAP, of the model insects Drosophila melanogaster and Spodoptera frugiperda, respectively, are rapidly depleted and thereby inactivated upon infection with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 54 publications
3
56
0
Order By: Relevance
“…3B, lanes 3 and 4). Confirming the efficacy of zVAD-fmk, virus-induced processing of the Drosophila effector caspase DrICE to its active large and small subunits (27,64) was fully blocked (compare lanes 3 and 4). We concluded that the DDR was caspase independent and thus triggered by vDNA replication-dependent events upstream of apoptosis.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…3B, lanes 3 and 4). Confirming the efficacy of zVAD-fmk, virus-induced processing of the Drosophila effector caspase DrICE to its active large and small subunits (27,64) was fully blocked (compare lanes 3 and 4). We concluded that the DDR was caspase independent and thus triggered by vDNA replication-dependent events upstream of apoptosis.…”
Section: Resultsmentioning
confidence: 85%
“…4C). Active DrICE is a principal mediator of baculovirus-induced apoptosis in DL-1 cells (27,64). Ruling out the possibility that caffeine blocked virus entry or early gene expression, levels of intracellular IE1 were comparable up through 10 mM caffeine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations